Futsal’s Inside Human Sport Physiology : A Literatures Description - Yustika, Gaung Perwira (Journal of Physical Education Health and Sport, 2019)
Futsal is played with high intensity (indoor version of football played by 5 people per team). With the dimensions of the playing field 40 x 20 m and the infinite turnover, as well as the task of defense and attack constantly, futsal players perform activities with high intensity such as sprints, acceleration, deakselation and changes in the direction of the game, creating a separate burden to the body's physiological processes involves the aerobic and anerobic metabolic systems. With the fact this game is played with high intensity then the research data found the average pulse rate (HRaverage) reached 174 times per minute, so that it can reach 90% of the maximum pulse rate (HRmaximum) for 72% of game time. This exercise also requires cardiovascular adaptation of 85-90% of the maximum pulse rate per individual. As for aerobic capacity to fulfill oxygen availability alone, the recommended VO2 max value is in the range of 50-55 ml / kg / minute is the recommended range for a minimum of professional futsal athletes. With more and more playing experience, the knowledge and training patterns practiced by futsal athletes make physical and physiological needs to support the performance of the game be fulfilled.